A glimpse at team composition and intention to grow in academic spin-offs. Issue 2 (3rd April 2022) - Tagliazucchi, Giulia; Balboni, Bernardo; Marchi, Gianluca
ABSTRACT: Starting from the description of the main traits of the academic environment within which this peculiar form of new venture is born, the authors question—in light of the presented results about the growth rates of a national sample of academic spin-offs—whether and how the intention to grow expressed by the academic entrepreneur influences the composition of the team, and more specifically the integration of nonacademic knowledge and experience—as a vector of a higher growth rate within the target market. In particular, the research question to be answered is: Does the integration of nonacademic team members in the early stages tie with a higher intention to grow of the academic entrepreneur? The contribution is configured as a work in progress, and it introduces an advancement about team formation process. Implications for practitioners relate to the key role of team composition in fostering growth of academic spin-offs.